Experimental Investigation of Heat Transfer in a Bubbling Fluidized Bed for Geldart A And B Particles - Ahmmad Shukrie, Md Yudin; Shahrani, Anuar; Azim, Arshad (2014)
The high rate of heat transfer achieved in fluidized-bed combustion is one of the most promising features of this technology as compared to pulverized or stoked coal combustion. The constant circulation of high heat capacity particles past an immersed heat transfer surface enhances the gas convection heat transfer to the immersed surface enormously, and particle convection has consequently been the subject of many studies in an attempt to understand its mechanistic details. The effects of temperature variations between an electrically heated tube immersed vertically in fluidized bed and sand particles of various sizes were experimentally studied. In this paper, the data for heat transfer coefficient for an electrically heated vertical tube immersed vertically in fluidized bed of sand particles ( ̅= 100, 177 and 250 m) is reported at temperature ranging from 50oC to 250oC. The temperature profiles for heater surface were recorded fairly uniform at all operations as a result of constant increment of voltage. Further, the temperature profiles of bed seemed to be rather uniform and characterized by small temperature gradient but gradual drop of bed temperature gradient for higher size particles was detected at higher operating temperature. The average heat transfer coefficient increases with increasing gas velocity towards a maximum value of the coefficient. The result also shows that the value of maximum heat transfer coefficient decreases with increase in particle diameter due to increase in gas conduction path and decreases in particle surface area per unit volume for heat exchange with the heater surface. An increase in operating pressure as the fluidizing gas velocity is progressively increased i.e. when the gas flow conditions are in the transitional or turbulent flow regime could be expected to lead to reduction in the overall heat transfer coefficient because of a possible increase in continuous phase voidage and hence reduction in particle packing density at the heat transfer surface.